2000
DOI: 10.1088/0953-8984/12/15/319
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the ferroelectric transition character of partially deuterated triglycine selenate

Abstract: Automatically recorded hysteresis loops and dielectric constant data on pure and partially deuterated triglycine selenate and sulphate are used to characterize the transition evolution from quasi-tricritical to clearly first order character. A quantitative assessment of the transition's displacive degree is made through the first anharmonic contribution to the effective field ( g ), obtained from hysteresis loop data. This characterization is complemented with the assessment by means of a generalized Rhodes-Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…[1,2]. Recently, we performed a calorimetric study on the phase transition showing that the specific heat of the ferroelectric phase follows a classical tricritical Landau potential whose coefficients have been determined [3].The effect of deuteration on the dielectric properties of phase transition in TGSe has been previously investigated [4][5][6]. It has been found that the thermal hysteresis as determined from dielectric-constant measurements increases when the deuteration increases, which indicates that the transition becomes first order.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2]. Recently, we performed a calorimetric study on the phase transition showing that the specific heat of the ferroelectric phase follows a classical tricritical Landau potential whose coefficients have been determined [3].The effect of deuteration on the dielectric properties of phase transition in TGSe has been previously investigated [4][5][6]. It has been found that the thermal hysteresis as determined from dielectric-constant measurements increases when the deuteration increases, which indicates that the transition becomes first order.…”
mentioning
confidence: 99%
“…The effect of deuteration on the dielectric properties of phase transition in TGSe has been previously investigated [4][5][6]. It has been found that the thermal hysteresis as determined from dielectric-constant measurements increases when the deuteration increases, which indicates that the transition becomes first order.…”
mentioning
confidence: 99%
“… is dipole moment of O-H··O bond, E is external electric field, V is spin lattice interaction and A k and B k are position and momentum operators, ω k is the harmonic phonon frequency V (3) and V (4) are third and fourth order atomic force constant.…”
Section: Model Hamiltonianmentioning
confidence: 99%
“…Recently Sun et al [3] have done growth and study about pyroelectric properties of pure and doped TGS crystal. Arago and Gonzalo [4] have done hysteresis curve studies of TGS crystal. Tolstekhina et al [5] have done atomic force microscopy domain structure on nano scale studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim is to analyze the possible changes with composition [2] of the main ferroelectric parameters in these partially deuterated compounds using the effective field approach [3] that is, expressing the field that experiences each dipole as the external electric field applied and the mean contribution of all other dipoles in the crystal, E eff = E + βP.…”
Section: Introductionmentioning
confidence: 99%